The role of pulse oximetry in the diagnosis of cardiopulmonary complications of ERCP - Emin ALTIPARMAK,; Orhan SEZGİN,; Yıldıran SONGÜR,; Yasemin KOŞAR,; Ülkü SARITAŞ,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-